La remuneración del docente del cantón Latacunga - Toaquiza Ayala, Cristian David (2017)
The educational system in Ecuador tends to generate gradual changes in the structure of this, which generates a satisfaction of the educational service that fulfills, and this is projected to satisfy the social, cultural academic needs in the daily exchange of teachers and students, for this reason The objective of this research was to diagnose the current situation on the remuneration of the teacher of the canton Latacunga, establishing bibliographical information to support the research generating a methodological procedure for the collection of data obtained that provide starting points for the situational diagnosis in which The educator is immersed as a professional who performs actions in the good of other beings that exist to the education of the Ecuadorian system. For this reason it has been necessary to present three specific objectives such as: to investigate bibliographical sources regarding the remuneration of teachers within the educational context, to design the methodological procedure of the investigation for the collection of statistical data and to analyze the results of Data obtained for the elaboration of conclusions and recommendations with respect to the work investigated....